Empu Krt. Subandi Suponingrat Keris Preservation in Documentary Photography - Atnin, Sepba Fri; Handriyotopo (East Asian Journal of Multidisciplinary Research, 2023)
Keris is one of the wealth objects in Indonesia which currently still exists and the process of making it can still be studied. The activity of making keris, which is often seen from childhood, is one of the ideas for creating this photographic work. This visual work uses documentary photography and applies EDFAT method. Documentary photography is a style of photography that depicts an event or situation that has important and historical meaning. Implementing EDFAT method helps to clarify the flow of a documentary photography story in creating this final project. The aim of creating this final assignment is to increase the existence of the Keris-making process among the younger generation.